2014
DOI: 10.1155/2014/480732
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Anti-R. equiHyperimmune Plasma againstR. equiChallenge in Thoroughbred Arabian Foals of Mares Vaccinated withR. equiVaccine

Abstract: This study aimed to determine the effectiveness of a pregnant mare immunization of a Rhodococcus equi (R. equi) vaccine candidate containing a water-based nanoparticle mineral oil adjuvanted (Montanide IMS 3012) inactive bacterin and virulence-associated protein A (VapA), as well as the administration of anti-R. equi hyperimmune (HI) plasma against R. equi challenge in the mares' foals. The efficacy of passive immunizations (colostral passive immunity by mare vaccination and artificial passive immunity by HI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The disease is of considerable importance to the equine industry [ 5 , 7 ], and while some reports indicate vaccination and/or passive transfer of hyperimmune plasma using bactrin-based or virulence associated protein A vaccines can reduce the severity of R . equi pneumonia [ 8 , 9 ], it is generally felt that most attempts to date to create an effective R . equi vaccine have been unsuccessful [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disease is of considerable importance to the equine industry [ 5 , 7 ], and while some reports indicate vaccination and/or passive transfer of hyperimmune plasma using bactrin-based or virulence associated protein A vaccines can reduce the severity of R . equi pneumonia [ 8 , 9 ], it is generally felt that most attempts to date to create an effective R . equi vaccine have been unsuccessful [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the latest papers also indicated that the effectiveness of this strategy might be dose-dependent, because 2 L of HIP was more beneficial than administration of 1 L or less of the same product [ 57 ]. What is more, when two methods: vaccination of mares and administration of HIP were used, clinical sings in the foals occurred later, were less severe and mortality rate was lower [ 65 ]. As it has been previously confirmed, clinical signs of pneumonia in foals can be associated with significantly higher fecal shedding of Rhodococcus equi .…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Vaccinations against R. equi are wildly awaited and often considered a form of prophylaxis. Unfortunately, despite many trials none of them was claimed effective enough to become commercially available [ 65 ]. Up to now there are no vaccinations available neither for mares nor for the foals [ 62 ].…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Administration of hyperimmune plasma to foals during the first few days and then again at 3 weeks of age is reported to reduce the incidence and severity of the disease. A recent study has shown that the immunization of pregnant mares with R. equi vaccine candidate having aqueous medium based nanoparticle mineral oil adjuvinated inactive bacterin and VapA along with administration of anti-R. equi hyperimmune plasma in foals may be effective in protection of foals from R. equi infection (Erganis et al 2014). Bordin et al (2014) have studied the immunogenicity of an electron beam inactivated R. equi vaccine in foals.…”
Section: Prevention and Control Strategies Prevention In Equines And mentioning
confidence: 99%